Cryo-attenuated properties of Tilia miqueliana pericarps and seeds - Wu, Yu; Sun, Xiao Rui; Peng, Chen Yin; Shen, Yong Bao; Visscher, Anne M.; Pritchard, Hugh W.; Wang, Ming Zhu; Deng, Zhi Yun (Frontiers in Plant Science, 2023)
Introduction Cryo treatment of dry seeds is known to attenuate the structure of fruit and seed coats, but little is known about the microstructural impacts of such treatment. The seeds of Tilia miqueliana are dispersed within a hard pericarp, the manual removal (hulling) of which is time-consuming and inefficient. Rapid hulling technology is urgently needed for sustainable production and convenience of edible nuts. Methods We explored the mechanistic basis of liquid nitrogen (N)-treatment weakening of the pericarp of T. miqueliana fruits using a range of microscopical, biophysical and chemical approaches. Results Liquid N treatment (40 s) resulted in lower pericarp contents of cellulose and hemicellulose, and increased amounts of lignin. Profound changes in cell structure and mechanical properties included the emergence of large holes and gaps between the mesocarp and endocarp cells. Also, the toughness of the pericarp decreased, whilst the hardness and brittleness increased, thereby changing the fracture type from ductile to brittle. Liquid N treatment of dry fruits followed by tapping with a hammer, reduced the number of damaged seeds three-fold and pericarp peeling time four-fold compared with manual hulling, whilst seed viability was not negatively affected. Discussion Comparable findings for the efficient and economical removal of hard covering structures from dispersal units of five more species from three other families following liquid N treatment indicates the potential application of our findings to large-scale production of seeds and seedlings for breeding, forestry and conservation/restoration purposes. Furthermore, it introduces a novel concept for postharvest treatment and pre-treatment of deep processing in nuts.